Latinx writing Los Angeles : nonfiction dispatches from a decolonial rebellion - López-Calvo, Ignacio; Valle, Victor M. (University of Nebraska Press, 2018)
Latinx Writing Los Angeles offers a critical anthology of Los Angeles's most significant English-language and Spanish-language (in translation) nonfiction writing from the city's inception to the present. Contemporary Latinx authors, including three Pulitzer Prize winners and writers such as Harry Gamboa Jr., Guillermo Gómez-Peña, and Rubén Martínez, focus on the ways in which Latinx Los Angeles's nonfiction narratives record the progressive racialization and subalternization of Latinxs in the southwestern United States. While notions of racial memory, coloniality, biopolitics, internal colonialism, cultural assimilation, Mexican or pan-Latinx cultural nationalism, and transnationalism permeate this anthology, contributors advocate the idea of a contested modernity that refuses to accept mainstream cultural impositions, proposing instead alternative ways of knowing and understanding. Featuring a wide variety of voices as well as a diversity of subgenres, this collection is the first to illuminate divergent, hybrid Latinx histories and cultures. Redefining Los Angeles's literary history and providing a new model for English, Spanish, and Latinx studies, Latinx Writing Los Angeles is an essential contribution to southwestern and borderland studies.